Hidden cause of paralysis: tight filum terminale in spinal cord injury without radiographic abnormality - Yuan, Yi; An, Zong Jian; Gao, Fei; Li, Zhi Hui; Xu, Wei Li; Sun, Yong (Frontiers in Pediatrics, 2025)
ObjectiveTo explore the clinical characteristics and surgical treatment outcomes of spinal cord injury without radiographic abnormality (SCIWORA) in children.MethodsA retrospective analysis was conducted on the clinical data of four children diagnosed with SCIWORA who were admitted to the Neurosurgery Department of Qingdao Women and Children's Hospital from November 2022 to June 2024. All four pediatric patients underwent laminectomy for spinal canal decompression along with resection of the filum terminale. Postoperatively, a regimen including corticosteroids and mannitol was administered. Following hospital discharge, each child was subjected to clinical follow-ups, and the neurological recovery from spinal cord injury was evaluated utilizing the American Spinal Injury Association (ASIA) impairment scale.ResultsAmong the four patients, there was one male and three females, aged from 3 years and 2 months to 8 years. Two cases were due to low falls, one from a lower back injury, and one from a lumbar sprain. All patients had thoracolumbar injuries, with rapid progression of symptoms, including paralysis, sensory impairment, and urinary and fecal retention. Follow-up duration ranged from 3 to 24 months; three patients showed varying degrees of recovery in muscle strength and/or sensory function and bowel and bladder control, while one showed no improvement. One patient developed scoliosis and another presented with neurogenic bladder.ConclusionTethered cord syndrome may be a potential underlying cause of SCIWORA. For children with SCIWORA accompanied by tethered cord syndrome, we recommend early surgical intervention to perform laminectomy and release the tethered cord, which may aid in the recovery of neurological function.